TRANSITION OF STAGE TECHNIQUES FROM SHAKESPEAREAN TO MODERN AGE - Sharma, Neha (International Journal of Research -GRANTHAALAYAH, 2015)
There are several techniques employed in presenting any art form. Stage is one of the most important element among these technique. It is the medium where one can show the talent and skills in front of audience. A place where selection, designing, adaptation and modification of any performance takes place is called stage. The stages used from ancient to modern age are the symbols of inheriting art and tradition of a generation to another generations. It can also be said that the visual detailing of any play, drama or art form can be technically performed on stage.